Implementasi Model Inquiry Training pada Pembelajaran Fiqh di SMP Islam Khoiru Ummah Malang - Ceni Amalia Ayu Lestari; Abdul Bashith; Mohamad Zubad Nurul Yaqin (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This study aims to describe the implementation of the Inquiry Training model in Fiqh learning for grade IX students at SMP Islam Khoiru Ummah Malang. A qualitative case study approach was employed, with data collected through observation, semi-structured interviews with one Fiqh teacher and eight students, and documentation. Data were analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that the implementation of Inquiry Training followed Joyce’s five syntaxes: problem presentation, data verification, experimentation, data organization, and reflection. However, the practice remained at the guided inquiry level. The teacher acted as a facilitator but still dominated the learning process, limiting students’ autonomy. Supporting factors included the relevance of Fiqh materials to students’ daily lives, the teacher’s guiding role, and analytical exercises. Inhibiting factors were students’ fatigue, unstructured discussions, low participation, weak argumentation based on religious evidence, and non-metacognitive reflection. The study concludes that Inquiry Training effectively promotes active and contextual Fiqh learning. Strengthening investigative worksheets, forming heterogeneous groups, and enhancing metacognitive reflection are needed to advance toward independent inquiry.